Retrieving the Real Frederick May (Journal of the Society for Musicology in Ireland, 2019)
Although Frederick May (1911–85) is seen as holding an important position in the history of twentieth-century composition in Ireland, writing about May has been sporadic. There exists no serious biographical study to date and most of the commentary on the music has been superficial and frequently misleading. Utilizing the recently re-catalogued collection of May’s manuscripts in the Manuscripts and Archives Research Library in Trinity College Dublin (TCD) and also libraries and public collections in Cork, the United States, London, the Czech Republic and Vienna as well as a number of private archives, this essay attempts to build a clearer picture of Frederick May. It also clarifies May’s position on a number of issues that have been misrepresented or omitted in the literature to date. This essay aims to provide a more reliable basis from which future studies of May’s music and the development of his style can draw.